Records of the Department of State relating to political relations between Siam and other states, 1910-1929 (NARA ;, 1910)
Instructions to and despatches from diplomatic officials, notes between the Department of State and foreign diplomatic representatives in the U.S., memos from the State Department , correspondence with officials of other government departments, and correspondence with private firms and persons. The despatches are often accompanied by enclosures.